Lazarus - Kepler, Lars (Kepler, Lars. Joona Linna novel., 2020)
"The latest installment in the internationally best-selling Joona Linna series sees the Swedish detective on the trail of the worst serial killer he's seen yet. Across the continent, someone is brutally murdering Europe's worst criminals. Who can object to taking out rapists, arsonists, human traffickers? But when two of the victims have a direct connection to detective Joona Linna, it's clear to him that somebody's trying to send him a message. His longtime colleague Saga Bauer dismisses his hunch as paranoid ravings, but all evidence points to a killer who they previously thought could only haunt their dreams. As innocent bodies begin to pile up in Sweden, the race is on to track down the most terrifying villain they've ever encountered"--